Introduction: The Autonomy of EU Law, Legal Theory and European Integration - Justin Lindeboom; Ramses A. Wessel (European Papers, 2024)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(3), 1247-1254 | Article | (Table of Contents) I. The autonomy of EU law and legal theory: bridging the disconnect. – II. Overview of this Special Section. | (Abstract) The autonomy of EU law is a source of ample connections between EU law and legal theory. This Special Section contributes to the mutual enrichment between EU constitutional law and legal theory – which traditionally have been mostly disconnected disciplines – by bringing together new, theory-informed perspectives on the autonomy of EU law and European integration from both EU lawyers and legal theorists. The ten Articles in this Special Section are grouped together in three categories, focusing re-spectively on philosophy of law, legal theory and legal history, and legal doctrine and the role of the European Court of Justice. Together, they provide a plethora of contrasting and complementary legal-theoretical views on the autonomy of EU law and the EU legal order, within the broader context of European integration. With this Special Section, we aim to contribute to the legal-theoretical analysis of EU constitutional law, hoping that many others will follow in our footsteps.